ANALISIS KEPUASAN PELANGGAN LABORATORIUM KLINIK PADA UNIT PELAKSANA TEKNIS DINAS LABORATORIUM KESEHATAN DAERAH KOTA BOGOR - Giri Winawirawan; R. Akhmad Munjin; Irma Purnamasari (Jurnal Governansi, 2017)
The purpose of this study are:  1) to describe how customer satisfaction of clinic lab of Technical Implementing Units Labkesda of Bogor City, 2) to know what obstacles that influence satisfaction factors of UPTD clinic lab. 3) to know any effort to give satisfaction of lab clinic customers in UPTD Labkesda of Bogor City.The method used in this research is descriptive qualitative that is to get the description of services in UPTD Labkesda by direct interview with respondents: Head of UPTD of labkesda, Sub division of Administration. Meanwhile for customer is given questionnaire about general data, experience and expectation after they become patients of UPTD Labkesda. In this study is the patient population as many as 238 people who visit each month. The samples taken based on Taro Yamane formula are 70 respondents as samples.The results of the analysis can be seen from the interviews from the head of UPTD Labkesda, administrative head office, employees and respondents obtained the majority of customer satisfaction UPTD Labkesda are good although there are many gaps between the expectation and reality in terms of customer satisfaction so that UPTD Labkesda tobe better and satisfy the consumers. Based on interviews and questionnaires were constrained things that become obstacles in satisfying the patient, among others, in terms of registration is still doing manually, reporting results or certificates of the test is still manual so that there are many mistakes, the collection of blood specimens that narrow, security and comfort of the space that is perceived as inadequate seen from the condition of many buildings collapsed, the examination parameters are less in number so as to reduce patient satisfaction, equipment conditions are relatively old when the completion of work that does not match, toilets that are less clean, the presence of an officer who sometimes is not in place, the parking lot that does not available, and the price issue to be paid because can not use the BPJS card.In order to increase patient satisfaction are suggested to UPTD Labkesda of Bogor City to use laboratory information system so that from registration to out of test result can minimize error using adequate software, existence of action to undisciplined employees, adaptation to city government of bogor to spend fund for maintenance and repair facilities and infrastructure that exist so as to increase customer satisfaction.Keywords: Customer, Customer Satisfaction, Satisfaction